1982
DOI: 10.1111/j.1365-246x.1982.tb06388.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetometer array studies and deep Schlumberger soundings in the Damara orogenic belt, South West Africa

Abstract: A zone of concentrated induced electric currents crossing parts of Zimbabwe, Botswana and South West Africa was discovered during a magnetovariational study conducted in 1972. In 1977, a second study was made with 27 recording magnetometers distributed across the width of South West Africa between latitudes 19 and 22's. Several geomagnetic disturbances were recorded with high recording efficiencies. Three of these time sequences were digitized for analysis. Magnetograms and Fourier transform amplitude and phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…A decade later, Losecke et al (1988) detected some highly conductive layers in the Lower Zambezi Valley and in the Zambezi Mobile Belt, for which the authors suggested a link to the conductive structures of the Damara Belt (e.g. de Beer et al, 1982bBeer et al, , 1976Beer et al, , 1975. These early MT measurements were supplemented by a first audio-magnetotelluric profile farther west through the Mana Pools Basin (Whaler and Zengeni, 1993).…”
Section: Making a Continent -Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A decade later, Losecke et al (1988) detected some highly conductive layers in the Lower Zambezi Valley and in the Zambezi Mobile Belt, for which the authors suggested a link to the conductive structures of the Damara Belt (e.g. de Beer et al, 1982bBeer et al, , 1976Beer et al, , 1975. These early MT measurements were supplemented by a first audio-magnetotelluric profile farther west through the Mana Pools Basin (Whaler and Zengeni, 1993).…”
Section: Making a Continent -Case Studiesmentioning
confidence: 99%
“…In addition to deep geo-electric experiments, magnetometer array studies were conducted over extensive regions (de Beer et al, 1982b). de Beer et al (1976) revealed a zone of concentrated induced currents at lithospheric depth crossing Namibia, Botswana and Zimbabwe based on a reversal in the vertical magnetic field at periods of ∼ 1, 000 − 10, 000 s. The inferred east-west trending zone of high electrical conductivity was found to be approximately 100 km wide in Namibia and widening towards western Zimbabwe to 250 km.…”
Section: Pioneering Em Work In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…found that their deepest, most conductive layer, had >1 S m p l conductivity. This is even larger than the typically high values inferred in other mobile belts of southern Africa (de Beer, Gough & van Zijl 1975;de Beer et al 1976de Beer et al , 1982ade Beer, van Zijl & Gough 1982b), although only the longitudinal conductance (thickness-conductivity product) of these good conductors is constrained. The sediments in the Mana Pools basin are thought to be several kilometres thinner (Orpen et af.…”
Section: Introductionmentioning
confidence: 67%
“…On the escarpment, the resistivity is higher at all depths. The Mana Pools basin thus appears to be a continuation of the good conductor running from Namibia into western Zimbabwe identified by de Beer (1982a), and provides a link to another beneath the Lower Zambezi basin to the east of Mana Pools, discovered magnetotellurically by Losecke, Knodel & Muller (1988). Comparisons between the geoelectrical model and other available results for the region are presented.…”
mentioning
confidence: 74%